2019
DOI: 10.1186/s40560-019-0417-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation in critically ill traumatic brain injury patients attenuates muscle atrophy, neurophysiological disorders, and weakness: a randomized controlled trial

Abstract: BackgroundCritically ill traumatic brain injury (TBI) patients experience extensive muscle damage during their stay in the intensive care unit. Neuromuscular electrical stimulation (NMES) has been considered a promising treatment to reduce the functional and clinical impacts of this. However, the time needed for NMES to produce effects over the muscles is still unclear. This study primarily aimed to assess the time needed and effects of an NMES protocol on muscle architecture, neuromuscular electrophysiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 51 publications
4
32
0
2
Order By: Relevance
“… 8 , 9 In this study, the subjects showed minimal change in the thickness of the VL muscle. The results of this report support previous findings 8 , 11 , 13 and suggest that the use of EMS to treat muscles with paralysis seems safe and feasible in the early phase of NMO.…”
Section: Discussionsupporting
confidence: 90%
“… 8 , 9 In this study, the subjects showed minimal change in the thickness of the VL muscle. The results of this report support previous findings 8 , 11 , 13 and suggest that the use of EMS to treat muscles with paralysis seems safe and feasible in the early phase of NMO.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find associations with systemic inflammatory response, but with the large variability in pro-inflammatory state of ICU patients, no clear implications can be generated about potential protective effects. This is in line with recent work [ 30 ] on limb muscle FES in ICU patients and with data in healthy subjects demonstrating that the effects of FES are similar to those of mild exercise [ 31 ], i.e., inhibiting pro-inflammatory cytokines [ 32 ]. Furthermore, Hickmann et al [ 33 ] showed that early exercise during the onset of septic shock did not enhance inflammation and preserved muscle mass.…”
Section: Discussionsupporting
confidence: 90%
“…So far, different ergometers have been developed allowing to record evoked force in response to ES and/or MS in ICU patients on three muscle groups (Fig. 2 c–e): adductor pollicis [ 12 , 13 , 55 ], ankle dorsiflexors [ 15 , 56 ] and quadriceps [ 14 , 57 , 58 ].…”
Section: Evoked Forcementioning
confidence: 99%
“…To overcome these limitations, non-volitional techniques combining electrical [ 12 ] or magnetic [ 13 ] stimulation applied to a motor nerve or over a muscle belly [ 14 ] with force measurements on a dedicated bedside ergometer have emerged in the field of ICU. This allows to record evoked-force in fully sedated patients, so that measurement can be performed early after ICU admission ( i.e.…”
Section: Introductionmentioning
confidence: 99%